2016
DOI: 10.2500/aap.2016.37.3971
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and laboratory characteristics of acute spontaneous urticaria and its progression to chronic spontaneous urticaria

Abstract: The patients with ASU who progressed toward CSU were characterized by a positive ASST result, thyroid autoimmunity, and profound basopenia at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…No significant difference in the prevalence of elevated IgG‐anti‐TG and/or IgG‐anti‐TPO was observed between patients with CSU and patients with acute urticaria, urticarial vasculitis, rheumatoid arthritis, or systemic lupus erythematosus . In contrast, some studies showed that patients with CSU had significantly higher levels of IgG antithyroid AAbs compared to patients with acute and chronic inducible urticaria. The difference in IgG antithyroid AAb levels was not statistically significant when CSU patients with atopic diseases were compared to nonatopic CSU patients .…”
Section: Resultsmentioning
confidence: 95%
“…No significant difference in the prevalence of elevated IgG‐anti‐TG and/or IgG‐anti‐TPO was observed between patients with CSU and patients with acute urticaria, urticarial vasculitis, rheumatoid arthritis, or systemic lupus erythematosus . In contrast, some studies showed that patients with CSU had significantly higher levels of IgG antithyroid AAbs compared to patients with acute and chronic inducible urticaria. The difference in IgG antithyroid AAb levels was not statistically significant when CSU patients with atopic diseases were compared to nonatopic CSU patients .…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, this was one of the first studies comparing ASST positivity among AU and CSU patients. In PubMed search with key words of AU and ASST, there was only one research paper published by Magen et al [8]. They reported ASST positivity as 63.4% in the CSU, and 23.3% in the AU group.…”
Section: Frequency Of Asst Positivitymentioning
confidence: 99%
“…Acute urticaria (AU) which lasts shorter than 6 weeks, has identifiable aetiology only in 50% of patients. General laboratory studies are not indicated in AU, however etiologic examination including ASST was shown to presume progression toward CSU [8].…”
Section: Introductionmentioning
confidence: 99%
“…In transitioning to urticaria, one of the most challenging and poorly understood cutaneous diseases for which the allergist/immunologist offers expertise, Magen et al 11 sought to identify clinical and laboratory patient attributes that may be predictive of the progression of acute spontaneous urticaria to chronic spontaneous urticaria. By studying 114 patients with acute urticaria without identifiable causes, the researchers reported that patients with acute spontaneous urticaria who progressed toward chronic spontaneous urticaria were characterized by a positive autologous serum skin test, thyroid autoimmunity, and profound basophilopenia at baseline.…”
Section: P Hysicians and Patients Often Have Different Viewsmentioning
confidence: 99%